2021
DOI: 10.1002/ctm2.515
|View full text |Cite
|
Sign up to set email alerts
|

New strategy for suppressing the growth of lung cancer cells harboring mutations in the ATP‐binding region of EGFR by targeting the molecular motor MYO1D

Abstract: In this study, we describe that the molecular motor MYO1D holds both wild-type and mutant EGFRs in the plasma membrane via interaction of MYO1D with a C-terminal portion of the kinase domain (C-terminal substrate-binding lobe or C-lobe) that does not contain the ATP-binding region. Further, we show that the knockdown of MYO1D suppresses the growth, invasion and downstream signals of lung cancer and glioblastoma cells expressing mutant EGFR or mutant ErbB2, which have resistance to afatinib, osimertinib, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…34,35 Ko and colleagues reported that the proliferation, motility, and survival of nonsmall-cell lung cancer cells were obviously reduced when MYO1D was knocked down, resulting in reduced cytomembrane levels of EGFR or mutant ERBB2 after MYO1D deficiency. 36 A previous study reported that MYO1D binds to the nonphosphorylated domain of the EGFR family and anchors it to the cytomembrane to avoid degradation, while overexpressed MYO1D activates the downstream RTK signaling pathway by upregulating EGFR on the tumor cytomembrane. 23 EGFR signaling is activated in multiple tumors, such as lung cancer, colorectal cancer, and leukemia, and it plays a key role in tumorigenesis and progression by promoting various cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Ko and colleagues reported that the proliferation, motility, and survival of nonsmall-cell lung cancer cells were obviously reduced when MYO1D was knocked down, resulting in reduced cytomembrane levels of EGFR or mutant ERBB2 after MYO1D deficiency. 36 A previous study reported that MYO1D binds to the nonphosphorylated domain of the EGFR family and anchors it to the cytomembrane to avoid degradation, while overexpressed MYO1D activates the downstream RTK signaling pathway by upregulating EGFR on the tumor cytomembrane. 23 EGFR signaling is activated in multiple tumors, such as lung cancer, colorectal cancer, and leukemia, and it plays a key role in tumorigenesis and progression by promoting various cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic and membrane fractions were prepared by a subcellular protein fractionation kit for cultured cells (Thermo Scientific) as previously described. 24 Each fraction was resolved by SDS–PAGE and probed for KITENIN by tagging antibodies to V5 and Myc. Fraction purity was analysed by probing for tubulin for the cytoplasm and Na + –K + ATPase for the membrane protein.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 The combination of fused mitochondrial structure is associated with increased ATP generation and reduced ROS levels, whereas fragmented mitochondrial structure results in mitochondrial uncoupling, decreased mitochondrial membrane potential and impaired ATP production, ultimately leading to apoptosis. 9 Deletion of the p53 gene causes mitochondrial oxidative phosphorylation and glycolysis, thus impairing metabolic reprogramming and mitochondrial metabolic function in malignant cells. 10 Activating pro-apoptotic factors and inducing mitochondrial outer membrane permeabilization are important functions of p53.…”
Section: Introductionmentioning
confidence: 99%
“…These factors lead to impaired energy metabolism, loss of control over cell differentiation and growth and disruptions in the cell cycle 7,8 . The combination of fused mitochondrial structure is associated with increased ATP generation and reduced ROS levels, whereas fragmented mitochondrial structure results in mitochondrial uncoupling, decreased mitochondrial membrane potential and impaired ATP production, ultimately leading to apoptosis 9 …”
Section: Introductionmentioning
confidence: 99%